Pat Romanello and Rose Albanese Wedding
Photograph of Pat Romanello and Rose Albanese Wedding party. Top left to right: Michelina "Lena" Carozza Talesfore, Tony Romanello, Pat Romanello, Rosie Albanese, Fanny ?, and Christine "Tiny" Albanese. Bottom left to right: Flora Albanese Talesfore, Angie Vitale, Sal Talesfore, Carrie DiSalvo